(untitled) (Annals of Medical Research, 2022)
Aim: Pulmonary thromboembolism (PTE) is a cause of high mortality and morbidity. The incidence of PTE increases over times. In the current study, we aimed to investigate the seasonal variation of PTE patients in Malatya, Turkey by using meteorological data. Materials and Methods: Total of 207 PTE patients were included in the study. All meteorological data; atmospheric pressure, humidity, temperature changes and wind speed were recorded. Results: In the current study, 113 (54.5%) patients were female and 94 (45.5%) patients were male. We diagnosed PTE most often in the autumn season. When the monthly distribution of patients was examined; the diagnosis was made most frequently (11.6%) in July and the least in February (4.3%). There was no statistically significant difference between the seasons and months in terms of the incidence of PTE (p> 0.5). The seasons pressure, temperature and humidity values were compared with each other, statistically significant difference was found (p = 0.00). There was a negative correlation between temperature and pressure and humidity. The frequency of PTE in patients without risk factors for PTE was examined by months. In these groups, PTE was most frequently diagnosed in May (11% n: 10) and least frequently diagnosed in July (2%, n: 3). There was no statistically significant difference between the seasons and months in terms of the incidence of patients with no risk factor for PTE (p> 0.5).